Shadow economies and corruption all over the world: revised estimates for 120 countries - Friedrich G. Schneider; Andreas Buehn (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
Estimations of the shadow economies for 120 countries, including developing, Eastern Europe and Central Asian and high income OECD countries over 1999 to 2006 are presented. The average size of the shadow economy (as a percent of "official" GDP) in 2004/05 in 76 developing countries is 35.5%, in 19 Eastern and Central Asian countries 36.7% and in 25 high income OECD countries 15.5%. An increased burden of taxation and social security contributions, combined with labour market regulations are the driving forces of the shadow economy. Furthermore, the results show that the shadow economy reduces corruption in high income countries, but increases corruption in low income countries. Finally, the various estimation methods are discussed and critically evaluated.
Keywords: O17; O5; D78; H2; H11; H26; 330; Shadow economy of 120 countries; tax burden; tax moral; quality of state institutions; regulation; MIMIC and other estimation methods; Schattenwirtschaft; Steuerbelastung; Steuermoral; Wirtschaftswachstum; Übergangswirtschaft; Schätzung; Welt; Entwicklungsländer; Osteuropa; OECD-Staaten